Method for preparing salt-tolerant brick body from waste incineration fly ash and coral aggregate and product thereof
By soaking and carbonizing coral aggregates and combining them with garbage leachate and garbage incineration fly ash, cementitious materials are formed, which solves the technical difficulty of combining garbage incineration fly ash and cement, and achieves efficient resource utilization and produces high-quality preparation The performance of salt-resistant bricks solves the problems of waste incineration fly ash treatment and environmental pollution.
Patent Information
- Application Number
- CN202411341691.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-27
AI Technical Summary
The waste incineration fly ash contains toxic and harmful substances, which are difficult to deal with, and its combination with cement will inhibit the hydration reaction and limit its resource application in the field of building materials; coral aggregates have good biocompatibility and permeability. However, there is technical difficulty when combined with waste incineration fly ash.
Coral aggregate is soaked in garbage leachate, and then carbonized, mixed with garbage leachate and garbage incineration fly ash, calcined and ground into powder, combined with cement and auxiliary material powder to form a gelled material, and salt-resistant bricks are prepared after mold curing.
It has realized the efficient resource utilization of waste incineration fly ash and garbage leachate, and prepared salt-resistant bricks with high uniaxial compressive strength and low strength loss rate of salt-immersed test pieces, which significantly improved the durability and environmental friendliness of the bricks. sex.
Smart Images

Figure CN119191791A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a salt-resistant brick body by utilizing fly ash from garbage incineration and coral aggregate and a product thereof, belonging to the field of resource utilization of hazardous wastes. Background Art
[0002] With the acceleration of global urbanization, the output of domestic waste has increased dramatically, and waste disposal has become one of the important issues in urban management. As a waste disposal technology with high efficiency and significant volume reduction effect, waste incineration has been widely used in many countries and regions. The fly ash produced during waste incineration contains toxic and harmful substances such as heavy metals, chloride salts, and dioxins. It also has high permeability and high leaching toxicity. If it is not handled properly, it will cause serious harm to the environment. Fly ash particles are small and have a large specific surface area. Heavy metal elements are very easy to leach from fly ash and enter the environment through rainwater runoff, groundwater seepage and other channels, causing pollution to soil and water bodies. Fly ash from waste incineration contains a high content of chloride salts, which mainly comes from chlorine-containing organic matter such as plastics and rubber in the garbage. Chloride salts are easy to form corrosive solutions in a humid environment, causing corrosion damage to metal pipes, equipment and other infrastructure. Dioxins are a type of persistent organic pollutants (POPs) produced during waste incineration, which are extremely carcinogenic, teratogenic and mutagenic. Although the content of dioxins in fly ash is relatively low, due to its high toxicity and difficulty in degradation, its potential threat to the environment and human health cannot be ignored. Therefore, in-depth research on the environmental hazards and resource utilization of fly ash from waste incineration is of great significance for achieving the sustainable development of waste incineration technology.
[0003] In the oceans of tropical or subtropical regions, there are a large number of coral islands and coral reefs. These islands and reefs are formed by the continuous thickening and expansion of coral skeletons composed of thousands of calcium carbonate during tens of millions of years of growth. These coral fragments provide a new type of building material for engineering construction-coral aggregate. Coral aggregate is light and porous, with good biocompatibility and durability. By mixing it with cement and other materials, coral concrete can be prepared. This concrete is not only high in strength, but also has excellent impermeability, corrosion resistance and durability, and is particularly suitable for engineering construction in marine environments and saline-alkali areas. Waste incineration fly ash contains a very high content of inorganic chloride salts, which not only inhibits the hydration reaction and seriously weakens the gelling properties of silicate cement, but also brings about a significant alkali back phenomenon, which seriously restricts its resource application in the field of building materials. There are great technical difficulties in the preparation of salt-resistant bricks using waste incineration fly ash. Therefore, considering the characteristics of the two materials, it is theoretically feasible to combine waste incineration fly ash and coral aggregate to prepare salt-resistant bricks. At the same time, the use of fly ash from garbage incineration and coral aggregate to prepare salt-resistant bricks has significant environmental protection significance. Through resource utilization, fly ash can be converted into valuable building materials to reduce its harm to the environment. As a natural resource, the impact of the mining and utilization of coral aggregate on the environment is relatively small. Therefore, the present invention helps to achieve the dual goals of resource utilization of waste and environmental protection. Summary of the invention
[0004] Purpose of the invention: The technical problem to be solved by the present invention is to provide a method and product for preparing salt-resistant bricks using waste incineration fly ash and coral aggregates with a simple preparation process.
[0005] Technical solution: To solve the above technical problems, the present invention provides a method for preparing salt-resistant bricks using fly ash from garbage incineration and coral aggregates, comprising the following steps:
[0006] (1) soaking coral aggregate in landfill leachate, separating solid from liquid, drying and carbonizing the separated soaked coral aggregate to obtain carbon-loaded aggregate;
[0007] (2) mixing the landfill leachate and the waste incineration fly ash, stirring them evenly, calcining them, and grinding them into powder to obtain fly ash active material powder;
[0008] (3) mixing cement, auxiliary material powder, and fly ash active material powder, stirring evenly, and obtaining a cementitious material; the auxiliary material powder is fly ash, red mud powder, or coal gangue powder;
[0009] (4) Mix the carbon-loaded aggregate and the cementitious material, add water, stir evenly, put into a mold, and cure to obtain a salt-resistant brick body.
[0010] The immersion time in step (1) is 0.5 to 2.5 hours, the uniaxial compressive strength of the prepared salt-resistant bricks is higher than 36 MPa, and the strength loss rate of the salt-immersion specimens is lower than 9.8%.
[0011] Wherein, the drying temperature in step (1) is 50-150°C.
[0012] Wherein, the carbonization temperature in step (1) is 350-550° C., and the carbonization time is 0.5-1.5 hours.
[0013] Wherein, the liquid-to-solid ratio of the landfill leachate and the landfill incineration fly ash in step (2) is 0.25-0.45:1 mL / g.
[0014] Wherein, the calcination time in step (2) is 0.5 to 1.5 hours, and the calcination temperature is 700 to 1100°C.
[0015] Among them, the mass ratio of cement, auxiliary material powder and fly ash active material powder in step (3) is 15-35:10-40:100, and the uniaxial compressive strength of the prepared salt-resistant bricks is higher than 40MPa, and the strength loss rate of the salt-immersed specimens is lower than 6.1%.
[0016] Wherein, the mass ratio of the carbon-loaded aggregate to the cementitious material in step (4) is 3 to 5:1, the uniaxial compressive strength of the prepared salt-resistant bricks is higher than 45 MPa, and the strength loss rate of the salt-immersed specimens is lower than 3.6%.
[0017] Wherein, the curing time in step (4) is 14 to 28 days.
[0018] Wherein, the mass ratio of water to gelling material in step (4) is 0.55-0.85:1 mL / g.
[0019] The invention also provides a salt-resistant brick body prepared by the method.
[0020] Reaction mechanism:
[0021] When coral aggregates are soaked in landfill leachate, a large amount of organic matter and inorganic ions contained in the landfill leachate will adhere to the surface of the coral aggregates and form a film on the surface of the coral aggregates. A small amount of organic acid will also cause corrosion on the surface of the coral aggregates, and calcium carbonate will dissolve to form tiny cavities. The aggregates soaked in leachate are introduced into a carbonization furnace for carbonization. Under high temperature, the organic matter adsorbed on the surface and pores of the coral aggregates decomposes to form a carbon-based surface covering the surface of the coral aggregates or filling the pores of the coral aggregates. At the same time, the acidic gas generated during the carbonization process will induce the surface material of the coral aggregates to dissolve and release calcium ions and carbon dioxide gas, thereby making the surface of the carbon-loaded coral aggregates rougher and forming more pores. The released calcium ions will react with the phosphates in the landfill leachate to form apatite minerals, which fill the pores of the carbon-loaded coral aggregates. Mix the landfill leachate and the fly ash from the incineration of garbage. The organic matter, ammonia nitrogen and phosphorus pollutants in the landfill leachate are adsorbed on the surface of the fly ash particles from the incineration of garbage, and the dissolution and reabsorption of soluble chloride salts in the fly ash are promoted. The organic acid in the landfill leachate will also react with the alkaline substances in the fly ash particles to produce an organic calcium precipitate. At the same time, the phosphate and ammonia nitrogen pollutants in the landfill leachate react with the slaked lime component in the fly ash from the incineration of garbage to produce a mixture of struvite, phosphate precipitation, hydroxyapatite and chlorohydroxyapatite. The mortar material is introduced into the furnace for calcination. During the calcination process, the organic matter and ammonia nitrogen pollutants in the landfill leachate are decomposed to form carbon dioxide and water vapor. The chloride in the fly ash is volatilized or oxidized with the organic pollutants to form alkaline substances, and the slaked lime is decomposed to form calcium oxide and water. Mix cement, auxiliary material powder and fly ash active material powder, and the three material components complement each other. Mix coral aggregate and cementitious materials, add water, and during the mixing process, cement combines with water to form a hydration reaction to form a bonding colloid. The mineral components in the auxiliary powder and the alkaline substances in the fly ash active material powder undergo self-excitation and self-gelation reactions to form a complex mixture of sodium calcium aluminosilicate geopolymers, Friedel salt, kuzel salt, calcium aluminate, and hydroxyapatite. The mixture and the bonding colloid fill each other and wrap the carbon-loaded aggregate. The hard surface of the carbon-loaded aggregate is rough, which is easier to combine with the gelling gel. The gelling gel fills the gaps and pores of the aggregate to form a highly salt-resistant brick.
[0022] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: the preparation process is simple, and the fly ash from garbage incineration and coral aggregate are used together to prepare highly salt-resistant bricks, which can achieve efficient resource utilization of fly ash from garbage incineration and leachate. The highest uniaxial compressive strength of the prepared brick is 46.79MPa, and the strength loss rate of the salt-immersed specimen is as low as less than 3%. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The present invention is a flow chart of the preparation method. DETAILED DESCRIPTION
[0024] The technical solution of the present invention is further described below in conjunction with the accompanying drawings.
[0025] Landfill leachate: The landfill leachate used in the experiment was obtained from Zhuji Sanfeng Environmental Protection Energy Co., Ltd. The COD mass concentration of this batch of concentrated landfill leachate was 3639 mg / L, the total phosphorus concentration was 294 mg / L, and the ammonia nitrogen concentration was 1062 mg / L;
[0026] Waste incineration fly ash: Waste incineration fly ash is provided by the Second Municipal Waste Incineration Power Plant in Changshu, Jiangsu Province, mainly including 38.14% CaO, 24.05% Cl, 10.21% SO3, 12.15% Na2O, 6.21% K2O, 3.17% SiO2, 1.41% Fe2O3, 1.19% Al2O3 and other components (loss on ignition and other inevitable impurities);
[0027] Red mud: Red mud was provided by Zibo Zhengheng Aluminum Co., Ltd. The main components tested include: 38.52% Fe2O3, 27.83% Al2O3, 12.49% SiO2, 11.36% Na2O, 5.61% TiO2, 0.57% CaO, 0.34% SO3 and other components (inevitable impurities and ignition loss);
[0028] Gangue: Gangue comes from Shanxi Xishan Coal and Electricity Co., Ltd., mainly including 46.87% SiO2, 33.51% Al2O3, 12.04% Fe2O3, 2.72% CaO, 2.36K2O, 1.37% TiO2 and other components (inevitable impurities and ignition loss);
[0029] Fly ash: from Taicang Power Plant of Huaneng Power International Co., Ltd., mainly including 43.21% SiO2, 27.08% Al2O3, 15.62% Fe2O3, 6.58% CaO, 3.42% TiO2, 1.43% SO3, 1.04% K2O, 0.63% Na2O and other components (unavoidable impurities and ignition loss);
[0030] Coral aggregate: Brand: Huiyue, from Huiyue Mineral Products Processing Plant in Lingshou County;
[0031] Cement: Type: Portland cement, Brand: Conch, Strength grade: 32.5R.
[0032] Example 1 Effect of coral aggregate immersion time on the performance of the prepared salt-resistant brick
[0033] The coral aggregate is soaked in the landfill leachate for 0.25 hours, 0.3 hours, 0.4 hours, 0.5 hours, 1.5 hours, 2.5 hours, 2.75 hours, 3 hours, and 3.25 hours, and the solid and liquid are separated. The separated soaked coral aggregate is dried to obtain the leachate soaked aggregate, wherein the drying temperature is 50°C. The leachate soaked aggregate is introduced into a carbonization furnace for carbonization to obtain carbon-loaded aggregate, wherein the carbonization temperature is 350°C and the carbonization time is 0.5 hours. The landfill leachate and the waste incineration fly ash are mixed according to a liquid-solid ratio of 0.25:1mL / g, and stirred evenly to obtain a mortar material. The mortar material is introduced into a furnace for calcination, and the calcined mortar material is ground into powder to obtain fly ash active material powder, wherein the calcination time is 0.5 hours and the calcination temperature is 700°C. Cement, auxiliary material powder, and fly ash active material powder are mixed in a mass ratio of 15:10:100, and stirred evenly to obtain a cementitious material, wherein the auxiliary material powder is fly ash. Carbon-loaded aggregate and cementitious material are mixed in a mass ratio of 3:1, water is added, stirred evenly, put into a mold, and cured for 14 days to obtain a salt-resistant brick body, wherein the mass ratio of the added water to the cementitious material is 0.55:1 mL / g.
[0034] Strength performance test: The 28d compressive strength of the salt-resistant brick body prepared in this embodiment is measured according to the "Test method for strength of cement mortar (ISO method)" GB / T 17671-1999 standard.
[0035] Calculation of seawater immersion and strength loss: The 28-day-old specimens were completely immersed in seawater for 30 days, and then the specimens were taken out for strength testing. The strength loss rate of the salt-immersed specimens was equal to the difference between the strength of the unimmersed 28-day-old specimens and the strength of the immersed specimens, divided by the percentage of the strength of the unimmersed 28-day-old specimens.
[0036] The test results of this embodiment are shown in Table 1.
[0037] Table 1 Effect of coral aggregate immersion time on the performance of prepared salt-resistant bricks
[0038] Coral Aggregate Soaking Time Uniaxial compressive strength of cement (MPa) Strength loss rate of salt immersion specimens 0.25 hours 22.32 18.21% 0.3 hours 26.46 16.57% 0.4 hours 30.58 13.46% 0.5 hours 36.41 9.72% 1.5 hours 39.02 7.55% 2.5 hours 40.83 6.14% 2.75 hours 35.37 10.36% 3 hours 32.79 12.75% 3.25 hours 28.52 15.08%
[0039] As shown in Table 1, when the coral aggregate soaking time is less than 0.5 hours (such as in Table 1, the coral aggregate soaking time = 0.4 hours, 0.3 hours, 0.25 hours and lower values not listed in Table 1), the coral aggregate soaking time is short, and the garbage leachate and the coral aggregate do not react fully, resulting in the uniaxial compressive strength of the prepared salt-resistant brick body significantly decreasing as the coral aggregate soaking time decreases, and the strength loss rate of the prepared salt-resistant brick body specimens significantly increases as the coral aggregate soaking time decreases. When the coral aggregate soaking time is equal to 0.5 to 1.5 hours (such as in Table 1, the coral aggregate soaking time = 0.5 hours, 1.5 hours, 2.5 hours), the coral aggregate is soaked in the garbage leachate, and a large amount of organic matter and inorganic ions contained in the garbage leachate will adhere to the surface of the coral aggregate and form a film on the surface of the coral aggregate. A small amount of organic acid will also cause corrosion on the surface of the coral aggregate, and calcium carbonate will dissolve to form tiny cavities. The aggregate soaked in leachate is introduced into the carbonization furnace for carbonization. Under high temperature, the organic matter adsorbed on the surface and pores of the coral aggregate decomposes to form a carbon-based surface covering the surface of the coral aggregate or filling the voids of the coral aggregate. At the same time, the acidic gas generated during the carbonization process will induce the surface material of the coral aggregate to dissolve and release calcium ions and carbon dioxide gas, thereby making the surface of the carbon-loaded coral aggregate rougher and forming more pores. The released calcium ions will react with the phosphate in the leachate to form apatite-like minerals, which fill the pores of the carbon-loaded coral aggregate. Finally, the uniaxial compressive strength of the prepared salt-resistant bricks is higher than 36MPa, and the strength loss rate of the salt-immersed specimens is lower than 9.8%. When the coral aggregate immersion time is greater than 2.5 hours (such as in Table 1, the coral aggregate immersion time = 2.75 hours, 3 hours, 3.25 hours and higher values not listed in Table 1), the coral aggregate immersion time is too long, the coral aggregate absorbs too much inorganic salt and corrodes excessively, resulting in the uniaxial compressive strength of the prepared salt-resistant brick body significantly decreasing as the coral aggregate immersion time further increases, and the strength loss rate of the prepared salt-resistant brick body specimens significantly increases as the coral aggregate immersion time further increases. Therefore, in general, combining benefits and costs, when the coral aggregate immersion time is equal to 1.5-4.5:100, it is most conducive to improving the performance of the prepared salt-resistant brick body.
[0040] Example 2 Effect of the mass ratio of cement, auxiliary material powder and fly ash active material powder on the performance of the prepared salt-resistant brick
[0041] Soak the coral aggregate in the landfill leachate for 2.5 hours, separate the solid and liquid, and dry the separated soaked coral aggregate to obtain the leachate-soaked aggregate, wherein the drying temperature is 100°C. Introduce the leachate-soaked aggregate into a carbonization furnace for carbonization to obtain carbon-loaded aggregate, wherein the carbonization temperature is 450°C and the carbonization time is 1 hour. Mix the landfill leachate and the fly ash from the garbage incineration at a liquid-solid ratio of 0.35:1mL / g, stir evenly, and obtain a mortar material. Introduce the mortar material into a furnace for calcination, grind the calcined mortar material into powder, and obtain fly ash active material powder, wherein the calcination time is 1 hour and the calcination temperature is 900°C. Cement, auxiliary material powder and fly ash active material powder are mixed in a mass ratio of 7.5:10:100, 10:10:100, 12.5:10:100, 15:5:100, 15:6:100, 15:8:100, 15:10:100, 25:10:100, 35:10:100, 15:25:100, 25:25:100, 35:25:100, 15:40:100, 25:40:100, 35:40:100, 35:45:100, 35:50:100, 35:55:100, 40:40:100, 45:40:100 and 50:40:100, and stirred evenly to obtain a cementitious material, wherein the auxiliary material powder is red mud powder. The carbon-loaded aggregate and the cementitious material are mixed in a mass ratio of 4:1, water is added, stirred evenly, put into a mold, and cured for 21 days to obtain a salt-resistant brick body, wherein the mass ratio of the added water to the cementitious material is 0.7:1 mL / g.
[0042] The strength performance test, seawater immersion and strength loss calculation are the same as in Example 1. The test results of this example are shown in Table 2.
[0043] Table 2 Effect of the mass ratio of cement, auxiliary powder and fly ash active powder on the performance of the prepared salt-resistant brick
[0044]
[0045]
[0046] It can be seen from Table 2 that when the mass ratio of cement, auxiliary material powder and fly ash active material powder is less than 15:10:100 (such as in Table 2, the mass ratio of cement, auxiliary material powder and fly ash active material powder = 15:8:100, 15:6:100, 15:5:100, 12.5:10:100, 10:10:100, 7.5:10:100 and lower ratios not listed in Table 2), less cement and auxiliary material powder are added, and the cement, auxiliary material powder and fly ash active material powder do not react fully, resulting in the uniaxial compressive strength of the prepared salt-resistant brick body significantly decreasing with the decrease of the mass ratio of cement, auxiliary material powder and fly ash active material powder, and the strength loss rate of the prepared salt-resistant brick body specimens significantly increasing with the decrease of the mass ratio of cement, auxiliary material powder and fly ash active material powder. When the mass ratio of cement, auxiliary powder and fly ash active powder is equal to 15-35:10-40:100 (as in Table 2, the mass ratio of cement, auxiliary powder and fly ash active powder = 15:10:100, 25:10:100, 35:10:100, 15:25:100, 25:25:100, 35:25:100, 15:40:100, 25:40:100, 35:40:100), the cement, auxiliary powder and fly ash active powder are mixed, and the three materials complement each other. Mix coral aggregate and cementitious material, add water, and during the mixing process, cement combines with water to react to form a bonding colloid. The mineral components in the auxiliary powder react with the alkaline substances in the fly ash active powder to undergo self-excitation and self-gelation reactions, generating a complex mixture of sodium calcium aluminosilicate geopolymers, Friedel salt, kuzel salt, ettringite, and hydroxyapatite. Ultimately, the uniaxial compressive strength of the prepared salt-resistant bricks was higher than 40MPa, and the strength loss rate of the salt-immersed specimens was lower than 6.1%. When the mass ratio of cement, auxiliary powder and fly ash active powder is greater than 35:40:100 (as in Table 2, the mass ratio of cement, auxiliary powder and fly ash active powder = 35:45:100, 35:50:100, 35:55:100, 40:40:100, 45:40:100, 50:40:100 and higher ratios not listed in Table 2), too much cement and auxiliary powder are added, and the reactions of the three materials are unbalanced, resulting in a significant decrease in the uniaxial compressive strength of the prepared salt-resistant brick body as the mass ratio of cement, auxiliary powder and fly ash active powder further increases, while the strength loss rate of the prepared salt-resistant brick body specimens significantly increases as the mass ratio of cement, auxiliary powder and fly ash active powder further increases. Therefore, in general, considering the benefits and costs, when the mass ratio of cement, auxiliary powder and fly ash active powder is equal to 15-35:10-40:100, it is most conducive to improving the performance of the prepared salt-resistant bricks.
[0047] Example 3 Effect of the mass ratio of carbon-loaded aggregate and cementitious material on the performance of the prepared salt-resistant brick
[0048] Soak the coral aggregate in the landfill leachate for 2.5 hours, separate the solid and liquid, dry the separated soaked coral aggregate to obtain the leachate soaked aggregate, wherein the drying temperature is 150°C. Introduce the leachate soaked aggregate into a carbonization furnace for carbonization to obtain carbon-loaded aggregate, wherein the carbonization temperature is 550°C and the carbonization time is 1.5 hours. Mix the landfill leachate and the fly ash from the garbage incineration at a liquid-solid ratio of 0.45:1mL / g, stir evenly, and obtain the mortar material. Introduce the mortar material into the furnace for calcination, grind the calcined mortar material into powder, and obtain the fly ash active material powder, wherein the calcination time is 1.5 hours and the calcination temperature is 1100°C. Mix cement, auxiliary material powder, and fly ash active material powder in a mass ratio of 35:40:100, stir evenly, and obtain a cementitious material, wherein the auxiliary material powder is coal gangue powder. Carbon-loaded aggregate and cementitious material are mixed in mass ratios of 2.25:1, 2.5:1, 2.75:1, 3:1, 4:1, 5:1, 5.25:1, 5.5:1, and 5.75:1, water is added, stirred evenly, put into a mold, and cured for 28 days to obtain a salt-resistant brick body, wherein the mass ratio of the added water to the cementitious material is 0.85:1 mL / g.
[0049] The strength performance test, seawater immersion and strength loss calculation are the same as in Example 1. The test results of this example are shown in Table 3.
[0050] Table 3 Effect of the mass ratio of carbon-loaded aggregate and cementitious material on the performance of the prepared salt-resistant brick
[0051]
[0052] It can be seen from Table 3 that when the mass ratio of carbon-loaded aggregate to cementitious material is less than 3:1 (such as in Table 3, the mass ratio of carbon-loaded aggregate to cementitious material = 2.75:1, 2.5:1, 2.25:1 and lower ratios not listed in Table 3), the carbon-loaded aggregate is added less, and the carbon-loaded aggregate and cementitious material react insufficiently, resulting in the uniaxial compressive strength of the prepared salt-resistant brick body significantly decreasing with the decrease of the mass ratio of carbon-loaded aggregate to cementitious material, and the strength loss rate of the prepared salt-resistant brick body specimens significantly increasing with the decrease of the mass ratio of carbon-loaded aggregate to cementitious material. When the mass ratio of carbon-loaded aggregate to cementitious material is equal to 3 to 5:1 (such as in Table 3, the mass ratio of carbon-loaded aggregate to cementitious material = 3:1, 4:1, 5:1), the mixture and the connecting colloid fill each other and wrap the carbon-loaded aggregate. The hard surface of the carbon-loaded aggregate is rough, which is easier to combine with the gelled gel. The gelled gel fills the gaps and pores of the aggregate to form a highly salt-resistant brick. Finally, the uniaxial compressive strength of the prepared salt-resistant bricks is higher than 45MPa, and the strength loss rate of the salt-immersed specimens is lower than 3.6%. When the mass ratio of carbon-loaded aggregate to cementitious material is greater than 5:1 (such as in Table 3, the mass ratio of carbon-loaded aggregate to cementitious material = 5.25:1, 5.5:1, 5.75:1 and higher ratios not listed in Table 3), the carbon-loaded aggregate is added too much, the cementitious material is not added enough, and the carbon-loaded aggregate and the cementitious material react insufficiently, resulting in the uniaxial compressive strength of the prepared salt-resistant brick significantly decreasing with the further increase of the mass ratio of carbon-loaded aggregate to cementitious material, and the strength loss rate of the prepared salt-resistant brick specimens significantly increasing with the further increase of the mass ratio of carbon-loaded aggregate to cementitious material. Therefore, in summary, considering the benefits and costs, when the mass ratio of carbon-loaded aggregate to cementitious material is equal to 3-5:1, it is most conducive to improving the performance of the prepared salt-resistant bricks.
[0053] Comparative example of the effects of different processes on the performance of salt-resistant bricks
[0054] The process of the present invention comprises the following steps: soaking coral aggregate in landfill leachate for 2.5 hours, separating solid from liquid, drying the separated soaked coral aggregate to obtain leachate-soaked aggregate, wherein the drying temperature is 150°C. The leachate-soaked aggregate is introduced into a carbonization furnace for carbonization to obtain carbon-loaded aggregate, wherein the carbonization temperature is 550°C and the carbonization time is 1.5 hours. The landfill leachate and the fly ash from the incineration of landfill are mixed at a liquid-solid ratio of 0.45:1 mL / g, stirred evenly, and a mortar material is obtained. The mortar material is introduced into a furnace for calcination, and the calcined mortar material is ground into powder to obtain fly ash active material powder, wherein the calcination time is 1.5 hours and the calcination temperature is 1100°C. Cement, auxiliary material powder, and fly ash active material powder are mixed at a mass ratio of 35:40:100, stirred evenly, and a cementitious material is obtained, wherein the auxiliary material powder is coal gangue powder. The carbon-loaded aggregate and the cementitious material are mixed in a mass ratio of 5:1, water is added, stirred evenly, put into a mold, and cured for 28 days to obtain a salt-resistant brick body, wherein the mass ratio of the added water to the cementitious material is 0.85:1 mL / g.
[0055] Comparative process 1: Mix the landfill leachate and the fly ash from the waste incineration at a liquid-solid ratio of 0.45:1 mL / g, stir evenly, and obtain a mortar material. Introduce the mortar material into a furnace for calcination, grind the calcined mortar material into powder, and obtain fly ash active material powder, wherein the calcination time is 1.5 hours and the calcination temperature is 1100°C. Mix cement, auxiliary material powder, and fly ash active material powder at a mass ratio of 35:40:100, stir evenly, and obtain a cementitious material, wherein the auxiliary material powder is coal gangue powder. Mix coral aggregate and cementitious material at a mass ratio of 5:1, add water, stir evenly, put into a mold, and cure for 28 days to obtain a salt-resistant brick body, wherein the mass ratio of water added to cementitious material is 0.85:1 mL / g.
[0056] Comparative process 2: Soak the coral aggregate in the leachate for 2.5 hours, separate the solid and liquid, dry the separated soaked coral aggregate to obtain the leachate soaked aggregate, wherein the drying temperature is 150°C. Introduce the leachate soaked aggregate into a carbonization furnace for carbonization to obtain carbon-loaded aggregate, wherein the carbonization temperature is 550°C and the carbonization time is 1.5 hours. Mix cement, auxiliary powder, and fly ash from garbage incineration in a mass ratio of 35:40:100, stir evenly, and obtain a cementitious material, wherein the auxiliary powder is coal gangue powder. Mix the carbon-loaded aggregate and cementitious material in a mass ratio of 5:1, add water, stir evenly, put into a mold, and cure for 28 days to obtain a salt-resistant brick body, wherein the mass ratio of water added to the cementitious material is 0.85:1mL / g.
[0057] The strength performance test, seawater immersion and strength loss calculation are the same as in Example 1. The test results of this comparative example are shown in Table 4.
[0058] Table 4 Effect of different processes on the performance of prepared salt-resistant bricks
[0059] Process Type Uniaxial compressive strength of cement (MPa) Strength loss rate of salt immersion specimens Process of the present invention 46.79 2.86% Comparison process 1 19.83 12.36% Comparison process 2 24.15 14.17%
[0060] It can be seen from Table 4 that the uniaxial compressive strength of the salt-resistant brick cement prepared by the process of the present invention is significantly higher than that of the salt-resistant brick prepared by comparison process 1 and comparison process 2, and the strength loss rate of the salt-immersion specimens of the salt-resistant brick prepared by the process of the present invention is significantly lower than that of the salt-resistant brick prepared by comparison process 1 and comparison process 2.
Claims
1. A method for preparing salt-resistant bricks using fly ash from garbage incineration and coral aggregates, characterized in that: The following steps are involved: (1) soaking coral aggregate in landfill leachate to separate solid from liquid, drying and carbonizing the separated soaked coral aggregate to obtain carbon-loaded aggregate; the soaking time is 0.5 to 2.5 hours; (2) mixing the landfill leachate and the waste incineration fly ash, stirring them evenly, calcining them, and grinding them into powder to obtain fly ash active material powder; (3) mixing cement, auxiliary material powder, and fly ash active material powder, stirring evenly, and obtaining a cementitious material; the auxiliary material powder is fly ash, red mud powder, or coal gangue powder; (4) Mix the carbon-loaded aggregate and the cementitious material, add water, stir evenly, put into a mold, and cure to obtain a salt-resistant brick body.
2. The method according to claim 1, characterized in that: The drying temperature in step (1) is 50-150°C.
3. The method according to claim 1, characterized in that: The carbonization temperature in step (1) is 350-550° C., and the carbonization time is 0.5-1.5 hours.
4. The method according to claim 1, characterized in that: The liquid-to-solid ratio of the landfill leachate and the landfill incineration fly ash in step (2) is 0.25-0.45:1 mL / g.
5. The method according to claim 1, characterized in that: The calcination time in step (2) is 0.5 to 1.5 hours, and the calcination temperature is 700 to 1100°C.
6. The method according to claim 1, characterized in that: The mass ratio of cement, auxiliary material powder and fly ash active material powder in step (3) is 15-35:10-40:
100.
7. The method according to claim 1, characterized in that: The mass ratio of the carbon-loaded aggregate to the cementitious material in step (4) is 3 to 5:
1.
8. The method according to claim 1, characterized in that: The curing time in step (4) is 14 to 28 days.
9. The method according to claim 1, characterized in that: The mass ratio of water to gelling material in step (4) is 0.55-0.85:1 mL / g.
10. A salt-resistant brick body prepared by the method according to any one of claims 1 to 9.
